Tinjauan Viktimologis Terhadap Korban Tindak Pidana Pencurian Kalung Emas Dengan Kekerasan Di Kampung Tunu Katega, Kecamatan Kota Waikabubak, Kabupaten Sumba Barat (Studi Kasus Di Kepolisian Resor Sumba Barat) - Zefanya Rambu Moha Lende Zefanya; Orpa Ganefo Manuain; Adrianus Djara Dima (CV. Ulil Albab Corp, 2026)
This study aims to analyze the role of victims and the forms of legal protection provided to victims in cases of violent gold necklace theft occurring in Kampung Tunu Katega, Waikabubak City District, West Sumba Regency. The research employs an empirical method with a case approach, using primary data obtained through interviews with investigators from the West Sumba Police and the victim, as well as secondary data from documents and relevant legal regulations. The results indicate that the victim’s role in the incident is situational, referring to certain conditions that indirectly create opportunities for the offender to commit the crime. These factors include wearing conspicuous gold jewelry in public places, the victim’s presence in public spaces without adequate supervision, and a lack of awareness of potential criminal threats. From a victimological perspective, the victim can be classified as an unrelated victim, precipitate victim, and victimizable. Furthermore, legal protection for the victim in this case has been partially implemented through compensation provided by the offender, facilitated by the police. However, the compensation did not fully cover the victim’s losses. The mechanisms of restitution and state compensation were not utilized due to their perceived complexity and lengthy procedures, leading the victim to prioritize the prosecution and punishment of the offender. This study concludes that legal protection for victims has not been fully effective, as it remains focused on punishing the offender, while the recovery of the victim has not been optimally fulfilled. Therefore, improvements in the implementation of victim protection mechanisms are necessary to achieve more balanced justice. .